Cultural Identity: The Symbols, Meaning, and Interpretation of Bakar Tongkang Tradition - Gusrini, Esi; Agustina; Efi, Agusti; Fitrisia, Azmi (Universitas Jambi, Indonesia, 2024)
This research looked at the background, history, and meaning related to this ritual and how culture plays an essential role in shaping the community identity. The Bakar Tongkang Ritual is a way for the Chinese community to express gratitude, honor their ancestors, and maintain their cultural identity. It also serves as a symbol of unity, commitment, and a way to connect with their faith and spirituality. It highlights the importance of symbols, meaning, and interpretation in ritual and how these elements are paramount in the overall cultural experience. The research method used a qualitative approach through observation, in-depth interviews, and documents. The results indicated a detailed exploration of the Bakar Tongkang ritual, its historical context, its significance in culture, and the related meanings. It underscores the importance of rituals in preserving cultural heritage, fostering unity, and expressing gratitude.